Presenting a Policy Implementation Model in the Field of Urban Management - Manteghi, Abolghasem; Forati, Hassan; Esmaeilnia Shirvani, Kambiz (Future of Work and Digital Management Journal, 2026)
This study was conducted with the aim of presenting a policy implementation model in the field of urban management. The data analysis method in the qualitative phase was based on the grounded theory approach and an exploratory–survey design. The statistical population consisted of 10 experts from the Semnan Province Municipality, who were selected through purposive sampling. The research instrument comprised semi-structured interviews. Data analysis was carried out using a three-stage coding process, including open coding, axial coding, and selective coding. The data obtained from semi-structured interviews with 10 experts were analyzed line by line, and the main and subcategories were extracted. Based on the findings, “intra-organizational characteristics affecting urban management policy implementation” were identified as the core category. Contextual conditions included policy principles, values, and norms, as well as the development of behavioral patterns. Causal conditions encompassed factors such as the creation of job attachment, motivation enhancement, justice and delegation of authority, learning, and employee empowerment. Intervening conditions included environmental stimuli, laws and regulations, cultural and social factors, and the economic and political conditions of the environment, all of which influenced policy implementation. In response to these conditions, the organization pursued a set of key strategies, including the formulation of a policy charter, adoption of a systematic approach, structural reform, institutionalization of policy culture, meritocracy, and the development of specialized training programs. The outcomes of successful policy implementation included the enhancement of meritocracy, realization of organizational justice, reduction of administrative corruption, improvement of performance evaluation, enhancement of the quality of urban services, and strengthening of leadership and organizational interactions. The final model of the study demonstrated that urban management policy implementation is a multidimensional process dependent on the dynamic interaction among individual, organizational, and environmental factors.